2004
DOI: 10.1111/j.1365-2222.2004.1938.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the ADAM33 gene are associated with accelerated lung function decline in asthma

Abstract: These findings suggest that a variant in ADAM33 is not only important in the development of asthma but also in disease progression, possibly related to enhanced airway remodelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
2
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(120 citation statements)
references
References 8 publications
5
109
2
4
Order By: Relevance
“…In this context, it is noteworthy that ADAM33 is selectively expressed in mesenchymal cells [76], strongly implicating it in airway remodelling. Consistent with this proposal, a rare allele of the S_2 polymorphism of ADAM33 is significantly associated with excessive decline in FEV1 in asthmatic subjects [82] and chronic obstructive pulmonary disease patients [83]. Furthermore, in a prospective birth cohort study, polymorphisms in ADAM33 predict impaired early-life lung function [84].…”
Section: Increased Deposition Of Extracellular Matrixsupporting
confidence: 61%
“…In this context, it is noteworthy that ADAM33 is selectively expressed in mesenchymal cells [76], strongly implicating it in airway remodelling. Consistent with this proposal, a rare allele of the S_2 polymorphism of ADAM33 is significantly associated with excessive decline in FEV1 in asthmatic subjects [82] and chronic obstructive pulmonary disease patients [83]. Furthermore, in a prospective birth cohort study, polymorphisms in ADAM33 predict impaired early-life lung function [84].…”
Section: Increased Deposition Of Extracellular Matrixsupporting
confidence: 61%
“…In recent studies, ADAMs have been suggested to play a role in a pulmonary disease like asthma [5][6][7][8][9] but also in interstitial lung disease [10], eosinophilic pneumonia [11], and lung cancer [12]. Moreover, single nucleotide polymorphisms (SNPs) in ADAM33 have been found to be associated with asthma development and progression [7] as well as with progressive lung function loss in the general population and development of COPD [13,14]. In view of the association of ADAMs with respiratory diseases, our study was undertaken to assess the expression and localization of various ADAMs with metalloproteinase activity (ADAM8, ADAM9, AD-AM10, ADAM17, ADAM19, and ADAM33) in human lung tissue.…”
Section: Introductionmentioning
confidence: 99%
“…54 Polymorphisms in ADAM33 are associated with a more rapid annual decline in postbronchodilator forced expiratory volume in one second (FEV1). 55 Such genetic associations may explain why severity and outcomes in adult asthma can to a certain extent be predicted in childhood and do not necessarily relate to inflammatory biomarkers. 56 Increased ASM numbers seem to be the cause rather than the consequence of severe disease in asthma.…”
Section: Restoration Of N Ormal Airway Structure (Mod Elling)mentioning
confidence: 99%